Title of Paper or Panel Goes Here - Last Name1, First Name1 Middle Name1; Last Name2, First Name2 Middle Name2 (AoIR Selected Papers of Internet Research, 2015)
Text of Abstract goes here - THIS information is included with the extracted data.